A comprehensive mixed-methods analysis of women’s cardiovascular health needs in Georgia, United States - Marlo Vernon; Brianna McIndoe; Michael J. Ryan; Amanda Behr; Daria Ilatovskaya; Ananya Chakraborty; Suma Yellamraju; Ara Idun; Jennifer Sullivan (Biology of Sex Differences)
Abstract Background and Aims In the United States, cardiovascular disease (CVD) is the leading cause of death among both men and women; CVD and associated risk factors particularly affect women who live in rural areas. This mixed-methods analysis aims to explore cardiovascular health (CVH) risk factors and healthcare experiences among women in rural Georgia, to identify barriers to care, and to inform strategies for improving long-term health outcomes in rural communities. Methods A convergent mixed methods design was utilized to evaluate CVH prevalence and associated environmental risk factors among women living in rural GA. Quantitative data from 159 Georgia counties were analyzed to compare rural and urban rates of CVD-related conditions and healthcare provider availability. Comparative analyses were performed between counties, urban and rural areas, and on sex differences. Concurrently, semi-structured interviews were conducted with 56 women and 11 healthcare providers to explore knowledge of blood pressure (BP) management, access to preventive services, and barriers to care. Qualitative and quantitative findings were analyzed separately and integrated during interpretation. Results Rural counties have significantly higher prevalence of hypertension, obesity and stroke. General trends revealed higher rates of smoking, physical inactivity, and excessive alcohol consumption in rural counties compared to rates in urban counties of GA. Qualitative themes revealed affordability concerns, communication challenges between patients and providers, limited trust in telehealth, and the importance of delivering CVH education in community-based settings. Differences by age were also observed: younger women expressed less concern or awareness about CVH risks, while older women described greater engagement with care and health information. While the original aim included gaps in awareness and education, participants primarily described navigating systemic barriers across the care continuum. Conclusion Rural women face individual, provider, and structural barriers to cardiovascular health and care. This unique study identifies chronic disease disparities and risk factors, with a higher disease burden observed in rural counties. Contributing factors may include limited resources for promoting healthy lifestyle choices, and reduced access to healthcare providers. Integrated findings underscore the need for sex- and gender- informed, age-specific, and community tailored strategies that address both health system access, and communication to improve CVH outcomes in underserved rural populations.